O uso das questões da OBMEP para a recuperação da aprendizagem matemática pós- pandemia: onde estamos e para onde vamos? - Silva, Paula Helena Novaes Moreira da (Universidade Federal de São Carlos, 2022)
In this dissertation we will use the question bank of the Brazilian Mathematics Olympiad of Public Schools and technological resources to work on the competences and skills of Geometry proposed by the National Common Curriculum and Curriculum Paulista for the 7th year of elementary school. The development of the work took place through the application of activity sheets in two classes of the 7th year of a public school in the interior of São Paulo, using technological products built and made available in GeoGebra, to support the solution of a closing activity sheet with a specific question of the aforementioned Olympiad.
The use of OBMEP questions for learning recovery post-pandemic mathematics: where we are and where are we going?
Keywords: OBMEP; BNCC; Currículo paulista; Recuperação da aprendizagem; Paulista curriculum; Learning recovery; CIENCIAS EXATAS E DA TERRA::MATEMATICA::GEOMETRIA E TOPOLOGIA